The determinants of innovation performance: An income-based cross-country comparative analysis using the Global Innovation Index (GII) - Adisu Fanta Bate; Esther Wanjiru Wachira; Sándor Danka (Journal of Innovation and Entrepreneurship, 2023)
Despite the dearth of research on innovation, the key determinants of innovation performance still need to be clarified. Besides, a comparative analysis of the determinants of innovation performance across countries at different income levels has yet to be found. This study, therefore, aims to bridge this research gap by considering the innovation performance of 63 countries. Participating countries were purposefully selected from the Global Innovation Index (GII) dataset. Multistage and multimodal analyses were conducted, including multiple linear regressions, hierarchical regression, and ANOVA, to examine the variation in innovation performance and pinpoint critical determinants in each category of countries. The result reveals that human capital, research, infrastructure, and business sophistication are the key pillars determining countries' innovation performance. In a variable-level analysis, innovation linkage and knowledge absorption (both of business sophistication), research and development (R&D), and infrastructure (inculcating both physical and digital) are the best predicting variables. The shortage of human capital to promote R&D is the biggest bottleneck hampering innovation in the lower-middle-income category. Also, both human capital for R&D activities and innovation linkage equally affect the upper-middle-income, and the latter one, innovation linkage, remains the main challenge even for the high-income category. The study implies that innovation performance predicts a country's economic growth. The level of innovation performance and the determinants of innovation vary per the countries' income levels. Accordingly, countries and firms in various income categories should prioritize tackling their respective bottlenecks hindering innovation performance in their policy directions. The study claims to have extended the horizon of understanding determinants of innovation across countries and revealed the most crucial factors in each category of countries. Further empirical comparative research can be done by incorporating an informal institution, national culture, as an additional determinant and specifying sectors across income categories.
Keywords: 650; Innovation; Infrastructure; Institutions; Human capital; Business sophistication; Determinants of innovation; Innovation inputs; Innovation outputs; Market sophistication; R&D